Comparative Osteological Biometrics and Morphology of Skull of the Snow Leopard (Panthera uncia) and Leopard (Panthera pardus) - Ram Noone, Sai; Sri Bairi, Navya; Gaikwad, Santosh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study was aimed to analyze the morphological, osteometric and clinically significant landmarks in the skulls of snow leopards and leopards. Skulls were processed through cold water maceration for clean bones, and differentiation was based on morphology and biometrics. Parameters such as length, width, curved length, curved width and cephalic index were measured using scales, Vernier calipers and thread. Results showed that the nasal cavity of the snow leopard was larger than that of the leopard. The angular process in snow leopards was 0.2 cm longer. Leopards had a groove between the orbital rims, while their tympanic bullae were rounder and more distended compared to the snow leopard. The snow leopard’s para-mastoid process formed a hook-like structure (0.5 cm long), and its supraorbital process was more pointed. This research provides species-specific characteristics useful for taxonomic classification, academic purposes, wildlife forensics and assisting wildlife veterinarians in handling clinical cases.